A state-dependent soil model and its application to principal stress rotation simulations - Zhongtao Wang; Peng Liu; Andrew Hin Cheong Chan (International Journal of Distributed Sensor Networks)
The plastic strain caused by principal stress rotation is one of the most important factors contributing to substantial deformation under earthquake, wave or traffic loading. The original Pastor–Zienkiewicz Mark III model, a well-known model for the analysis of the dynamic response under cyclic loading, is unable to consider the effects of principal stress orientation as well as state-dependent dilatancy. In this article, a new constitutive model for sand is developed to consider both aforementioned effects based on the original Pastor–Zienkiewicz Mark III model. There are 14 model parameters in total for the static condition and three extra parameters for cyclic loading, and a corresponding calibration method of model parameters is proposed. The predictive capability of the proposed model is verified with the results of a series of experiments on sand, including undrained monotonic tests in different fixed principal stress orientations and undrained cyclic rotational shear tests. The comparisons indicate that the proposed model can effectively incorporate the effects of principal stress orientation and state-dependent dilatancy.